Video games: Adicction and predictors - Vallejos, Miguel (2010)
Assesses the way relate the familiar and interactive styles (decision-making and tendency to risk) with the video game addiction among adolescents, as well as the consequences that generates addiction games assertiveness, aggressiveness and academic performance. It employed a stratified probability sample of schoolchildren in state secondary schools Metropolitan Lima, including schoolchildren of both sexes aged between 11 and 18 years. The results indicate that 85% of adolescents have access to video games, even if the boys play more than women, while women (70.6%) and men (94.7%) make use of high videogame. Notable among the places where the games are played the home (40%) and in the booths Internet (42%). As to the relationship between the use of video games and psychological variables (family functioning, decision making and aggressive behavior) are explained variability of the model is 14%, being the most important factor explaining the functionality family (ß = -0.256, p<0.01). We also found that the lower the greater assertiveness and aggressiveness then academic performance is low, relationships that are conditioned by the increased access or use of the games.